Nocturnal dispersal flight of crickets: Behavioural and physiological responses to cool environmental temperatures. (14th July 2020) - Sun, Bao‐Jun; Huebner, Christopher; Treidel, Lisa A.; Clark, Rebecca M.; Roberts, Kevin T.; Kenagy, G. J.; Williams, Caroline M.
Abstract: Flight of nocturnal insects may be limited by cool nighttime environmental temperatures. We used laboratory and field experiments to explore the thermal basis of nocturnal flight in wing‐polymorphic Gryllus lineaticeps crickets consisting of long‐winged (LW), flight‐capable morphs and short‐winged (SW), flight‐incapable morphs. These crickets are a model for life history evolution and loss of flight, but their thermal requirements for flight have been unknown. We hypothesized that LW crickets achieve warm body temperatures required for flight through a combination of behavioural thermoregulation, producing heat endogenously (either by initiating muscular thermogenesis or increasing resting metabolic rate) and minimizing heat loss (by circulatory adjustments or insulation). Summer evening air temperatures in the field gradually declined from 25 to 18°C during the hours of nighttime cricket activity. Laboratory LW crickets did not fly at a body temperature of 18°C, and 60% flew at 25°C. In an experimental thermal gradient, spontaneous flight did not occur until body temperature exceeded 35°C, confirming that nocturnal field air temperature limits flight in this species. In a thermal gradient, LW crickets preferred higher temperatures (~36°C) than SW crickets (~32.5°C). In the field, all crickets were warmer than air temperature but considerably cooler than their preferred temperatures. LW crickets had higher field body temperatures (24.3°C) than SW crickets (22.3°C). LW crickets spontaneously initiated muscular thermogenesis through wing vibrations, increasing body temperature to a pre‐flight maximum of 35°C. Muscular thermogenesis was limited below 25°C. LW crickets cooled more slowly and had higher metabolic rates than SW crickets. We conclude that LW crickets prepare to fly on cool nights by gaining heat from warm substrates, activating endogenous muscular thermogenesis and reducing their cooling rate. These mechanisms are absent or less pronounced in SW crickets. The overall thermoregulatory strategy we report represents a previously unrecognized component of insect dispersal polymorphism. We suggest that thermal constraints on nocturnal flight may have contributed to evolutionary loss of flight in other insect groups. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article .